2018
DOI: 10.1021/acsami.8b04496
|View full text |Cite
|
Sign up to set email alerts
|

Dual Suppression Effect of Magnetic Induction Heating and Microencapsulation on Ice Crystallization Enables Low-Cryoprotectant Vitrification of Stem Cell–Alginate Hydrogel Constructs

Abstract: Stem cells microencapsulated in hydrogel as stem cell-hydrogel constructs have wide applications in the burgeoning cell-based medicine. Due to their short shelf life at ambient temperature, long-term storage or banking of the constructs is essential to the "off-the-shelf" ready availability needed for their widespread applications. As a high-efficiency, easy-to-operate, low-toxicity, and low-cost method for long-term storage of the constructs, low-cryoprotectant (CPA) vitrification has attracted tremendous att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 61 publications
0
60
0
1
Order By: Relevance
“…Since β cells are easier available and capable of secreting insulin, their encapsulation in hydrogel could thus mimic real islet to regulate blood glucose. Different from the traditional islet cryopreservation methods including a high concentration of permeable cryoprotectants (pCPAs, like dimethyl sulfoxide, glycerol, ethylene glycol and propylene glycol) to prevent ice crystal damages, recent preservation methods enable efficient storage of various cells with hydrogel encapsulation, electromagnetic fields, nanoparticles, etc . Researches have been carried out and showed that by using droplet microfluidics numerous functional materials based on hydrogels could be fabricated .…”
Section: Introductionmentioning
confidence: 99%
“…Since β cells are easier available and capable of secreting insulin, their encapsulation in hydrogel could thus mimic real islet to regulate blood glucose. Different from the traditional islet cryopreservation methods including a high concentration of permeable cryoprotectants (pCPAs, like dimethyl sulfoxide, glycerol, ethylene glycol and propylene glycol) to prevent ice crystal damages, recent preservation methods enable efficient storage of various cells with hydrogel encapsulation, electromagnetic fields, nanoparticles, etc . Researches have been carried out and showed that by using droplet microfluidics numerous functional materials based on hydrogels could be fabricated .…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be attributed to the following: First, cryopreserved fat tissue is not only a dead filler. Some stem cells and capillary cells surrounding this tissue may have survived or become dormant temporarily, which is similar to the encapsulation and preservation of hydrogels made by Zhao [ 19 , 20 ]. With controlled cooling, stem cells and endothelial cells can be protected and retain their activity.…”
Section: Discussionmentioning
confidence: 92%
“…Mechanically, in addition to the cryopreservation provided by cryo-solution and alginate hydrogel, Fe 3 O 4 NPs uniformly present outside of hydrogel further suppressed devitrification and recrystallization during nanowarming process. Nanowarming was the primary reason for promoted attachment of thawed pADSCs [97]. This technology was also found to be efficient in human UC-MSCs and resulted in an improved vitrification outcome [98] (Fig.…”
Section: Rf Inductive Warming Processmentioning
confidence: 97%
“…Liu et al [97] successfully achieved low-CPA vitrification of stem cell-alginate hydrogel constructs by combining nanowarming and micro-encapsulation technology (Fig. 5a).…”
Section: Rf Inductive Warming Processmentioning
confidence: 99%